Matrix cross-linking lysyl oxidases are induced in response to myocardial infarction and promote cardiac dysfunction. (10th August 2015) - González-Santamaría, José; Villalba, María; Busnadiego, Oscar; López-Olañeta, Marina M.; Sandoval, Pilar; Snabel, Jessica; López-Cabrera, Manuel; Erler, Janine T.; Hanemaaijer, Roeland; Lara-Pezzi, Enrique; Rodríguez-Pascual, Fernando
Abstract: Aims: After myocardial infarction (MI), extensive remodelling of the extracellular matrix contributes to scar formation. While aiming to preserve tissue integrity, this fibrotic response is also associated with adverse events, including a markedly increased risk of heart failure, ventricular arrhythmias, and sudden cardiac death. Cardiac fibrosis is characterized by extensive deposition of collagen and also by increased stiffness as a consequence of enhanced collagen cross-linking. Members of the lysyl oxidase (LOX) family of enzymes are responsible for the formation of collagen cross-links. This study investigates the contribution of LOX family members to the heart response to MI. Methods and results: Experimental MI was induced in C57BL/6 mice by permanent ligation of the left anterior descending coronary artery. The expression of LOX isoforms (LOX and LOXL1–4) was strongly increased upon MI, and this response was accompanied by a significant accumulation of mature collagen fibres in the infarcted area. LOX expression was observed in areas of extensive remodelling, partially overlapping with α-smooth muscle actin-expressing myofibroblasts. Tumour growth factor-β as well as hypoxia-activated pathways contributed to the induction of LOX expression in cardiac fibroblasts. Finally, in vivo post-infarction treatment with the broadband LOX inhibitor β-aminopropionitrile or, selectively, with a neutralizing antibody against the canonical LOX isoform attenuated collagen accumulation and maturation and also resulted in reduced ventricular dilatation and improved cardiac function. Conclusion: LOX family members contribute significantly to the detrimental effects of cardiac remodelling, highlighting LOX inhibition as a potential therapeutic strategy for post-infarction recovery.